Detection of Buried Ancient Artifacts in Lembah Bujang, Kedah - Mohd Nordin, Mohd Nawawi (2009)
Lembah Bujang in Merbuk, Kedah is one of the designated archaeological sites in Malaysia. Buried ancient artifacts believed to be 3rd Century evidence have been successfully discovered by a group of Universiti Sains Malaysia scientists recently. This discovery was achieved by the contribution from the application of geophysical techniques apart from the reconnaissance archaeological survey carried out earlier. Electrical resistivity imaging and ground penetrating radar equipments were employed in this investigation. Subsurface targets have been detected and their locations and extends mapped precisely. Detailed land cover map of the site was derived from remote sensing data. SPOT imagery was used for the purpose. Data from magnetic measurements was then displayed in the form of a magnetic map. The composite of magnetic map layer and the satellite imagery was used to locate potential target areas. Data collected from these various techniques then formed the basis our geographic information system that led to the new successful archaeological discovery.